Structural convergence of web graph, social network and malaria network: an analytical framework for emerging web-hybrid search engine. (1st January 2014) - Eze, Monday; Labadin, Jane; Lim, Terrin
It is a well known truth that there is no malaria transmission without blood-sucking bites by mosquitoes. Since there is no blood-sucking without contacts, it follows that the contacts between human beings and mosquitoes can be exploited to generate contact networks. Active computational research in this area is geared at developing new frontiers in modelling malaria transmission through network theory and methods. Ongoing research in this area points to the fact that there are structural similarities between web graph, social network and malaria networks. It is the aim of this paper to explore the structural convergence and to exploit this to build a framework that will pave the way for developing web-hybrid search engines. Like the emergence of search engines revolutionised web research, it is expected that application of search engines in malaria research will make a tremendous impact in malaria control.